PRODUCTION OF CAULIFLOWER (Brassica oleracea var. Botrytis L.) DUE TO APPLICATION OF NPK DOSES AND CONCENTRATIONS OF RABBIT LIQUID ORGANIC FERTILIZER - Soebari, Erica; Sutini, Sutini; Augustien, Nora (International Journal of Multidisciplinary Research and Literature, 2024)
The community's need for cauliflower commodities is increasing and greater than the rate of food production, which has the potential to increase the food crisis. The purpose of the study was to determine the production of cauliflower plants due to the application of NPK fertilizer and Rabbit Liquid Organic Fertilizer. This study used a Factorial Randomized Group Design (4x4) with 3 replications. The first factor is the dose of NPK fertilizer consisting of 0 gr/plant (M0), 5 gr/plant (M1), 6.25 gr/plant (M2), and 7.5 gr/plant (M3). The second factor is the concentration of Rabbit LOF 0 ml/L (K0), 30 ml/L (K1), 45 ml/L (K2), 60 ml/L (K3). The results of the study are: 1) There is a real interaction in the treatment of NPK fertilizer doses and concentrations of LOF Rabbit effect on total chlorophyll in the leaves; 2) The effect of NPK fertilizer dosage has a real effect on harvest index and a very real effect on plant height and number of leaves; 3) The treatment of LOF Rabbit fertilizer dosage has a significant effect on the parameters of plant height and harvest index